Analyzing Loss Components in DC Generator for Wind Turbine Applications - Elysa Nensy Irawan; Kai Shibuya; Nguyen Hong Minh Giang; Rizky Hamdani Sakti (Journal of Mechatronics and Artificial Intelligence, 2024)
Direct current (DC) generators have gained attention for their simplicity and reliability in wind turbine applications. However, DC generators are subject to energy losses, including ohmic, magnetic core, and mechanical losses, which impact system performance. This research investigates these losses in DC generators used in wind turbines through experimental testing. The methodology integrates laboratory experiments with simulations to quantify and understand loss mechanisms. Findings offer insights for optimizing wind turbine efficiency and reliability. Results show significant total power loss of 99%, emphasizing the need for meticulous loss assessments. Friction, copper, and iron loss coefficients are analyzed with the value of 0.217 and 0.709, respectively. However, with the rise in input voltage levels, a noticeable pattern becomes evident, where the significance of iron loss decreases relative to other influencing factors. Understanding these dynamics is crucial for enhancing wind turbine performance and advancing sustainable energy solutions.